Clinical Utility of Anorectal Manometry in Children with Functional Constipation: Can Anorectal Manometry Help Predict the Therapeutic Response? - Dhiren Patel; Courtney Decker; Leonel Rodriguez (Children)
Background: Anorectal Manometry (ARM) plays a crucial role in diagnosing potential motility disorders of anorectum in pediatric gastroenterology. Despite its prevalence, the predictive utility of ARM in guiding therapeutic response remains poorly characterized. Objectives: This study aims to evaluate the effectiveness of ARM in predicting therapeutic responses among children with functional constipation. Methods: A retrospective chart review was conducted at two tertiary centers examining pediatric patients who underwent ARM between January 2018 and July 2022. Key ARM parameters were analyzed, including anal resting pressure, recto-anal inhibitory reflex (RAIR), first rectal sensation, and bear-down maneuver (BDM). Therapeutic responses were assessed post-ARM, with success defined as an increase in bowel movement frequency and/or a decrease in fecal incontinence. In addition, we also intended to evaluate the eventual need for surgical intervention as another outcome. Results: The study included 327 patients, with a median age of 8.2 years. The overall therapeutic response rate was 40.7%, with stimulant laxatives showing a 48% response. Notably, lower anal resting pressures and delayed rectal sensations were associated with better therapeutic outcomes. Abnormal BDM correlated with a lack of response to therapies, while the presence of abnormal RAIR was linked to a higher eventual need for surgical intervention. Conclusions: ARM is instrumental in predicting therapeutic responses in pediatric patients with functional constipation. In addition to diagnosing HD, ARM could be an instrumental tool in identifying patients with dyssynergic defecation for early intervention with targeted therapy in age-appropriate patients.